Leukotrienes in exhaled breath condensate and fractional exhaled nitric oxide in workers exposed to TiO2 nanoparticles - Pelclova, Daniela; Zdimal, Vladimir; Kacer, Petr; Fenclova, Zdenka; Vlckova, Stepanka; Komarc, Martin; Navratil, Tomas; Schwarz, Jaroslav; Zikova, Nadezda; Makes, Otakar; Syslova, Kamila; Belacek, Jaroslav; et al. (Journal of breath research, 2016)
Human health data regarding exposure to nanoparticles are extremely scarce and biomonitoring of exposure is lacking in spite of rodent pathological experimental data. Potential markers of the health-effects of engineered nanoparticles were examined in 30 workers exposed to TiO2 aerosol, 22 office employees of the same plant, and 45 unexposed controls. Leukotrienes (LT) B4, C4, E4, and D4 were analysed in the exhaled breath condensate (EBC) and urine via liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS). Fractional exhaled nitric oxide (FeNO) and spirometry was also measured. The median particle number concentration of the aerosol in the production ranged from 1.98 × 10(4) to 2.32 × 10(4) particles cm(-3); about 80% of the particles were <100 nm in diameter. Median total mass concentration varied between 0.4 and 0.65 mg m(-3). All LT levels in workers' EBC were elevated relative to the controls (p < 0.01). LTs in the EBC sample were correlated with titanium levels. Urinary LTs were not elevated in the workers and office employees. Office workers had higher LTB4 in EBC (p < 0.05), and higher levels of FeNO (p < 0.01). FeNO was higher in office employees with allergic diseases and was negatively correlated with smoking (p < 0.01). In spirometry significant impairment in the workers was seen only for %VCIN and %PEF (both p < 0.01). Multiple regression analysis confirmed a significant association between production of TiO2 and all cysteinyl LTs in EBC (p < 0.01) and impaired %VCIN and %PEF (both p < 0.01). LTB4 was also associated with smoking (p < 0.01). LT levels complemented our earlier findings of DNA, protein, and lipid damage in the EBC of workers with nanoTiO2 exposures. Cysteinyl LTs in EBC analysis suggest inflammation and potential fibrotic changes in the lungs; they may be helpful for monitoring the biological effect of (nano)TiO2 on workers. Spirometry was not sensitive enough.
Keywords: Regression Analysis; dospělí; Exhalation; aerosoly; Leukotrienes; biologické markery; Hydrogen-Ion Concentration; Biomarkers; Adult; Tandem Mass Spectrometry; Nanoparticles; pracoviště; lidé; Occupational Exposure; Titanium; regresní analýza; studie případů a kontrol; Breath Tests; nanočástice; titan; leukotrieny; Aerosols; tandemová hmotnostní spektrometrie; pracovní expozice; Case-Control Studies; Workplace; vydechnutí; oxid dusnatý; Respiratory Function Tests; dechové testy; respirační funkční testy; koncentrace vodíkových iontů; Nitric Oxide; Humans